2014
DOI: 10.1002/jbm.a.35332
|View full text |Cite
|
Sign up to set email alerts
|

Micropatterned coculture of vascular endothelial and smooth muscle cells on layered electrospun fibrous mats toward blood vessel engineering

Abstract: A major challenge in vascular engineering is the establishment of proper microenvironment to guide the spatial organization, growth, and extracellular matrix (ECM) productions of cells found in blood vessels. In the current study, micropatterned fibrous mats with distinct ridges and grooves of different width were created to load smooth muscle cells (SMCs), which were assembled by stacking on vascular endothelial cell (EC)-loaded flat fibrous mats to mimic the in vivo-like organized structure of blood vessels.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…endothelial cells and smooth muscle cells, tumor cells and endothelial cells, hepatocytes, fibroblasts and epithelial cells and corneal keratocytes and so on), to simulate the interaction between them. We use this system to study the complex interaction between cells [2427]. …”
Section: Discussionmentioning
confidence: 99%
“…endothelial cells and smooth muscle cells, tumor cells and endothelial cells, hepatocytes, fibroblasts and epithelial cells and corneal keratocytes and so on), to simulate the interaction between them. We use this system to study the complex interaction between cells [2427]. …”
Section: Discussionmentioning
confidence: 99%
“…To imitate native interfacial areas and to create cell gradients and transitional populations, multiphasic scaffolds are investigated ( Figure A,B), with a particular interest in skin, the osteochondral and bone‐to‐ligament/tendon interfaces . Modified topographies, patterned surfaces and anisotropic scaffolds were deemed to improve the functionality of specific cell types such as smooth muscle cells or neurons . However, controlling topography and porosity of the scaffold in the context of coculture is more challenging, as cocultured cells do not necessarily present the same physiological features.…”
Section: Key Considerations In Coculture Systemsmentioning
confidence: 99%
“…Smooth muscle cells (SMCs) are located either around the vessel wall forming a contractile vascular membrane, or in the surrounding ECM, aligned with the blood flow shear stress . Many diseases and injuries can lead to irreversibly damaged blood vessels . To achieve neovascularization in vivo, the rebuilding of smooth muscle tissues is therefore extremely important.…”
Section: Tissue‐specific Coculture Processesmentioning
confidence: 99%
“…Such patterning with adhesive molecules can be realized by several techniques. Commonly used are microcontact printing [53,155] dry lift-off [58,156], dip-pen nanolithography [157158], and block copolymer micelle nanolithography [159]. All these methods are just exemplary techniques allowing the (bio)chemical modification of structured surfaces for in vitro cell studies.…”
Section: Reviewmentioning
confidence: 99%
“…The most commonly used surface structure to study this phenomenon consists of arrays of ridges and grooves. Generally, cells orient preferably stronger along the direction of grooves and ridges, the narrower and deeper/higher these structures are [5,12,156,192,221225]. It was observed that few tenths of nanometers in structure depth was already sufficient for some cell types to trigger contact guidance [201202].…”
Section: Reviewmentioning
confidence: 99%